HUBUNGAN PEMERIKSAAN STATUS GIZI DENGAN KEJADIAN STUNTING PADA BALITA USIA 2-5 TAHUN DI KENAGARIAN SUNGAI DAREH WILAYAH KERJA PUSKESMAS SUNGAI DAREH TAHUN 2025 - Suriani, Rida; Mutia, Mutia; Fawziyah, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
According to the World Health Organization the prevalence of stunting in toddlers in Indonesia has decreased from 24.4% in 2021 to 21.6% in 2022. However, the figure still has not reached the national stunting target of 14% (WHO, 2020). The purpose of this study was to determine the relationship between nutritional status and the incidence of stunting in toddlers aged 2-5 years in Sungai Dareh Village, the working area of Sungai Dareh Health Center. The method used was an analytical survey using a cross-sectional study approach with a sample of 84 respondents. The sampling technique for this study used Accidental sampling is a technique for determining samples based on chance, that is, anyone who happens to meet the researcher can be used as a sample, if the person who was met by chance is deemed suitable as a data source. The instrument used was an observation sheet. Based on univariate analysis, the results showed that 42 toddlers (50%) had normal nutritional status, and 75 toddlers (89.3%) had normal stunting. Based on bivariate analysis using the Chi-Square test, the results showed that there was a relationship between nutritional status examination and the incidence of stunting in toddlers aged 2-5 years with a p value of 0.000 < 0.05. It is expected that the results of this study can be used as a reference for Sungai Dareh Health Center in improving the quality of health services, especially in examining nutritional status with stunting incidents.Keywords: Nutritional Status, Stunting, Toddlers